Using additional moderator to control the footprint of a COSMOS rover for soil moisture measurement - Badiee, Amir; Wallbank, John R.; Fentanes, Jaime Pulido; Trill, Emily; Scarlet, Peter; Zhu, Yongchao; Cielniak, Grzegorz; Cooper, Hollie; Blake, James R.; Evans, Jonathan G.; Zreda, Marek; Köhli, Markus; et al. (Water resources research, 2021)
Cosmic-Ray Neutron Probes (CRNP) have found application in soil moisture (SM) estimation due to their conveniently large (>100 m) footprints. Here, we explore the possibility of using high-density polyethylene (HDPE) moderator to limit the field of view, and hence, the footprint of a SM sensor formed of 12 CRNP mounted on to a mobile robotic platform (Thorvald) for better in-field localization of moisture variation. Ultra Rapid Adaptable Neutron-Only Simulation neutron scattering simulations are used to show that 5 cm of additional HDPE moderator (used to shield the upper surface and sides of the detector) is sufficient to (a) reduce the footprint of the detector considerably, (b) approximately double the percentage of neutrons detected from within 5 m of the detector, and (c) does not affect the shape of the curve used to convert neutron counts into SM. Simulation and rover measurements for a transect crossing between grass and concrete additionally suggest that (d) SM changes can be sensed over a length scales of tens of meters or less (roughly an order of magnitude smaller than commonly used footprint distances), and (e) the additional moderator does not reduce the detected neutron count rate (and hence increase noise) as much as might be expected given the extent of the additional moderator. The detector with additional HDPE moderator was also used to conduct measurements on a stubble field over three weeks to test the rover system in measuring spatial and temporal SM variation.
Gesehen am 19.07.2022